Crizotinib in c-MET- or ROS1-positive NSCLC: results of the AcSé phase II trial. (4th October 2019) - Moro-Sibilot, D; Cozic, N; Pérol, M; Mazières, J; Otto, J; Souquet, P J; Bahleda, R; Wislez, M; Zalcman, G; Guibert, S D; Barlési, F; Mennecier, B; et al.
Abstract: Background: In 2013, the French National Cancer Institute initiated the AcSé program to provide patients with secure access to targeted therapies outside of their marketed approvals. Efficacy and safety was then assessed using a two-stage Simon phase II trial design. When the study design was designed, crizotinib was approved only as monotherapy for adults with anaplastic lymphoma kinase plus non-small-cell lung cancers (NSCLC). Patients and methods: Advanced NSCLC patients with c-MET ≥6 copies, c-MET -mutated, or ROS-1 -translocated tumours were enrolled in one of the three cohorts. Patients were treated with crizotinib 250 mg twice daily. Efficacy was assessed using the objective response rate (ORR) after two cycles of crizotinib as primary outcome. Secondary outcomes included disease control rate at four cycles, best ORR, progression-free survival, overall survival, and drug tolerance. Results: From August 2013 to March 2018, 5606 patients had their tumour tested for crizotinib targeted molecular alterations: 252 patients had c-MET ≥6 copies, 74 c-MET -mutation, and 78 ROS-1 -translocated tumour. Finally, 25 patients in the c-MET ≥6 copies cohort, 28 in the c-MET -mutation cohort, and 37 in the ROS-1 -translocation cohort were treated in the phase II trial. The ORR was 16% in the c-MET ≥6 copies cohort, 10.7% in the mutated, and 47.2% in the ROS-1 cohort. The best ORR during treatment was 32% in the c-MET -≥6 copies cohort, 36% in the c-MET -mutated, and 69.4% in the ROS-1 -translocation cohort. Safety data were consistent with that previously reported. Conclusions: Crizotinib activity in patients with ROS1 -translocated tumours was confirmed. In the c-MET -mutation and c-MET ≥6 copies cohorts, despite insufficient ORR after two cycles of crizotinib, there are signs of late response not sufficient to justify the development of crizotinib in this indication. The continued targeting of c-MET with innovative therapies appears justified. Clinical trial number: NCT02034981.